High daily insulin exposure in patients with type 2 diabetes is associated with increased risk of cardiovascular events. Issue 2 (June 2015) - Stoekenbroek, R.M.; Rensing, K.L.; Bernelot Moens, S.J.; Nieuwdorp, M.; DeVries, J.H.; Zwinderman, A.H.; Stroes, E.S.; Currie, C.J.; Hutten, B.A.
Abstract: Aims: Intensive glucose control, often involving insulin treatment, failed to improve cardiovascular outcomes in several clinical trials. Observational studies reported an association between insulin use and cardiovascular disease (CVD) risk. It has therefore been suggested that insulin adversely affects CVD risk. To investigate the feasibility of this hypothesis, we studied the association between insulin dose and CVD risk in type 2 diabetes. Methods: A case-control study was conducted of new users of oral antidiabetics who were prescribed insulin, using the Dutch Pharmo database. Cases were hospitalized for a cardiovascular event (CVE) and matched 1:2 to patients who were not hospitalized for a CVE, by sex, age, duration of diabetes and type of oral antidiabetic. Patients were divided into tertiles according to mean daily insulin dose. Conditional logistic regression analyses were used to explore the association between insulin exposure and CVE risk. Results: We included 836 patients (517 (62%) male, mean age 66 years). After adjusting for available potential confounders, including HbA1c and triglycerides, insulin exposure was positively related to CVE risk (odds ratios for high (≥53.0 U/day) and intermediate (24.3–52.9 U/day) vs. low exposure (≤24.2 U/day): 3.00 [95% confidence interval (CI) 1.70 to 5.28] and 2.03 [95% CI 1.17 to 3.52]. Conclusion: Our findings are in line with the suggestion that high-dose insulin therapy adversely affects CVD risk, but need to be interpreted with caution due to the observational nature of the study. The role of particularly high-dose insulin in the progression of CVD warrants further investigation. Highlights: We studied the association between insulin dose and cardiovascular event risk. Daily insulin dose remains positively related to CVE risk after adjusting for confounders. The role of high-dose insulin therapy in the progression of CVD warrants further investigation.